Factors Influencing Students' Enthusiasm In Speaking Class - Nur, Nur Aliyah (English Language Teaching for EFL Learners Journal, 2019)
This research aimed to investigate the meaning of enthusiasm, to observe the responses of enthusiastic students to the speaking activities in the speaking class, and to investigate the factors influencing students’ enthusiasm in speaking class. This research belongs to qualitative and it is placed within the phenomenology approach as the collection of information was qualifiedly by examining the phenomena of the factors influencing students’ enthusiasm in speaking class at the 5th semester students of English Education Department at UIN Alauddin Makassar. The data were analyzed and interpreted by using “coding technique” which covered three types: open coding, axial coding, and selective coding. The findings showed that Enthusiasm has several meanings such as; feeling or emotion, excitement, eagerness and achieving. Enthusiasm has several functions like; energy enhancer, goal maintainer, curiosity gripper, interest presenter, fire igniters, fear reducer, worry dissolver, and apathy eliminator. There are eight characteristics of enthusiastic students, they are; happiness, curiosity, satisfaction, endurance in speaking, courage, intolerance, agreement, and assistance. The factors influencing students’ enthusiasm in speaking class are; the instructional materials used by the lecturers or teachers, the lecturer/teacher competence and performance, the students’ attitude during the speaking activities, and the classroom environment.